Penerapan Metode Double Exponential Smoothing dan Regresi Linier pada Peramalan Persediaan Packaging di PT. XYZ - Sherly Indriani Rahayu; Jauhari Arifin (Fakultas Teknik Universitas Tulang Bawang, 2023)
PT. XYZ is one of the company that produces packaging materials, one of which is sacks. This study aims to determine forecasting on sack raw material packaging using the Double Exponential Smoothing method and Linear Regression in these calculations using manual calculation methods using Microsoft excel. The two methods are then identified as having the smallest error value. The data used in this study uses secondary data in the form of sales reports of raw material packaging in the past. Based on the forecasting results obtained using the Double Exponential Smoothing and Linear Regression methods, the smallest error value was obtained in the linear regression method with an error value of 275,711. The forecasting results in the next period were 16,713 by manual calculation. Thus, among the predicted results of the two methods, the linear regression method is the most optical. Keywords: Double Exponential Smoothing; Forecasting; Regresi Linier